THE ROLE OF MAFINDO (MASYARAKAT ANTI FITNAH INDONESIA) IN MAINTAINING RELIGIOUS HARMONY - Okditazeini, Vannyora (Analisa: Journal of Social Science and Religion, 2022)
The use of the internet as a medium of communication and interaction was inevitable. Information could spread very quickly, especially on issues such as religion. This also has an impact on the spread of hoax information on the internet. In conjunction with this, many websites/virtual groups have emerged and they carried an “anti-hoax” movement that could filter information, for example, MAFINDO (Masyarakat Anti Fitnah Indonesia – it could be translated in English as Indonesian Anti-Hoax Society). This group adherently helped people clarify misinformation on their website or social media. Therefore, this paper discussed the role of the anti-hoax group in maintaining religious harmony. This research used content analysis to show some posts of this group on their social media. The results of this study indicate that anti-hoax group plays an important role as cyber-police that will help maintain a harmonious life of religion. First, becomes the mover who creates an active, peaceful, and prosperous civil society. Second, becomes the collaborator that cooperates with other parties in an effort to combat fraud and hatred. Third, synergizes as an enlightener to integrate all positive social aspects to create an enlightened society that is immune to hoax outbreaks. Lastly, as the main source which developed a strong, credible, and accountable organization. With this role, the public could be digitally literate about content and misinformation circulating in the community.